A new species of Onthophagus Latreille, 1802 (Coleoptera: Scarabaeidae: Onthophagini) in the subgenus Gibbonthophagus Balthasar, 1935 from the mountains of north-west Yunnan, China - Urban, Patrick (Zootaxa, 2026)
Onthophagus (Gibbonthophagus) draconisaurei Urban, sp. nov., from the Yunnan Province in China is described. Relevant diagnostic characters of the new species and of the types of O. (G.) balthasari Všetečka, 1939 as well as O. (G.) taurinus White, 1844 are photographically documented and compared in a character matrix. New taxonomic characters for the subgenus Gibbonthophagus Balthasar, 1935 are provided.